2020
DOI: 10.1016/j.jnutbio.2020.108466
|View full text |Cite
|
Sign up to set email alerts
|

Apple polyphenol-rich drinks dose-dependently decrease early-phase postprandial glucose concentrations following a high-carbohydrate meal: a randomized controlled trial in healthy adults and in vitro studies

Abstract: Apple polyphenol-rich drinks dose-dependently decrease early-phase postprandial glucose concentrations following a high-carbohydrate meal: a randomized controlled trial in healthy adults and in vitro studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 66 publications
0
9
1
Order By: Relevance
“…In vitro studies have revealed inhibitory effects of ferulic acid on starch digestion via interactions with amylopectin leading to the formation of cross-linked feruloyl amylopectin which may be related to suppression of glucose and insulin responses observed in vivo [54]. In contrast to previous studies showing inhibitory effects of apple polyphenol supplementation [40,46] and commercial apple juice [45] on GIP and GLP-1, we found no impact on these incretin hormones in this study. One recent study reported increased postprandial GLP-1 concentrations after pectin intake in mice [55]; therefore, it is possible that pectin in Renetta Canada apples counteracted any polyphenol mediated increase in GIP/GLP-1 concentrations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have revealed inhibitory effects of ferulic acid on starch digestion via interactions with amylopectin leading to the formation of cross-linked feruloyl amylopectin which may be related to suppression of glucose and insulin responses observed in vivo [54]. In contrast to previous studies showing inhibitory effects of apple polyphenol supplementation [40,46] and commercial apple juice [45] on GIP and GLP-1, we found no impact on these incretin hormones in this study. One recent study reported increased postprandial GLP-1 concentrations after pectin intake in mice [55]; therefore, it is possible that pectin in Renetta Canada apples counteracted any polyphenol mediated increase in GIP/GLP-1 concentrations.…”
Section: Discussioncontrasting
confidence: 99%
“…Oat β-glucans have also been implicated in reduced postprandial glycemic responses and improved glycemic control in patients with type 2 diabetes mellitus [41][42][43]. Furthermore, studies have shown beneficial effects of apples and their derivatives on postprandial glycemia and insulinemia [40,[44][45][46]. Apples contain between 66 (Fuji variety) to 212 (Renetta Canada variety) mg/100 g total polyphenols and are a rich source of fiber (approximately 2-3 g/100 g) mainly in the form of pectin [47].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, increased consumption of fruit juice, instead of whole fruits (particularly from blueberries, grapes, and apples), seems to lead to an increased risk of T2D development, as observed in a study where 187,382 health professionals were free of major chronic diseases at baseline [78]. However, in a double-blind crossover acute trial in 34 healthy adult subjects, it was demonstrated that apple drinks enriched with phlorizin-rich apple extract reduced plasma glucose levels [79]. Another double-blind crossover trial with 25 healthy adult subjects showed that apple phenolic compounds reduced postprandial insulin, C-Peptide, and the insulin area under the curve at 30 min after a high-carbohydrate meal [80].…”
Section: Phytochemical Compounds: Structure Food Sources Bioavailabil...mentioning
confidence: 97%
“…Apples are rich in bioactive polyphenols and were found to decrease postprandial blood glucose in two small randomized controlled trials [ 35 , 36 ] conducted in healthy subjects. However, a recent study of subjects who consumed apples on a regular basis did not show any improvements of fasting blood glucose or serum insulin when compared to controls [ 37 ].…”
Section: Specific Dietary Sources Of Polyphenols and Diabetes Riskmentioning
confidence: 99%
“… Apple Polyphenols reduce postprandial insulin, C-Peptide and insulin area under the curve at 30 min. Prpa E J et al [ 36 ] Double blind, crossover acute trial in 34 healthy subjects an in vitro study of possible mechanism. Evaluate the effect of Apple Extract (with different content of polyphenols and phlorizin) vs. placebo on post-prandial glucose.…”
Section: Table A1mentioning
confidence: 99%